Practical process control for engineers and technicians - Altmann, Wolfgang (Practical professional books from Elsevier., 2005)
This book is aimed at engineers and technicians who need to have a clear, practical understanding of the essentials of process control, loop tuning and how to optimize the operation of their particular plant or process. The reader would typically be involved in the design, implementation and upgrading of industrial control systems. Mathematical theory has been kept to a minimum with the emphasis throughout on practical applications and useful information. This book will enable the reader to: * Specify and design the loop requirements for a plant using PID control * Identify and apply the essential building blocks in automatic control * Apply the procedures for open and closed loop tuning * Tune control loops with significant dead-times * Demonstrate a clear understanding of analog process control and how to tune analog loops * Explain concepts used by major manufacturers who use the most up-to-date technology in the process control field A practical focus on the optimization of process and plant Readers develop professional competencies, not just theoretical knowledge Reduce dead-time with loop tuning techniques.